The Impact of Persistent Leukoencephalopathy on Brain White Matter Microstructure in Long-Term Survivors of Acute Lymphoblastic Leukemia Treated with Chemotherapy Only - Sabin, N.D.; Cheung, Y.T.; Reddick, W.E.; Bhojwani, D.; Liu, W.; Glass, J.O.; Brinkman, T.M.; Hwang, S.N.; Srivastava, D.; Pui, C.-H.; Robison, L.L.; Hudson, M.M.; et al. (American Journal of Neuroradiology, 2018)
BACKGROUND AND PURPOSE: Survivors of acute lymphoblastic leukemia are at risk for neurocognitive deficits and leukoencephalopathy. We performed a longitudinal assessment of leukoencephalopathy and its associations with long-term brain microstructural white matter integrity and neurocognitive outcomes in survivors of childhood acute lymphoblastic leukemia treated on a modern chemotherapy-only protocol.MATERIALS AND METHODS: One hundred seventy-three survivors of acute lymphoblastic leukemia (49% female), treated on a chemotherapy-only protocol, underwent brain MR imaging during active therapy and repeat imaging and neurocognitive testing at follow-up (median, 13.5 years of age; interquartile range, 10.7–17.6 years; median time since diagnosis, 7.5 years; interquartile range, 6.3–9.1 years). Persistence of leukoencephalopathy was examined in relation to demographic and treatment data and to brain DTI in major fiber tracts and neurocognitive testing at follow-up.RESULTS: Leukoencephalopathy was found in 52 of 173 long-term survivors (30.0%) and persisted in 41 of 52 (78.8%) who developed it during therapy. DTI parameters were associated with leukoencephalopathy in multiple brain regions, including the corona radiata (fractional anisotropy, P = .001; mean diffusivity, P < .001), superior longitudinal fasciculi (fractional anisotropy, P = .02; mean diffusivity, P < .001), and superior fronto-occipital fasciculi (fractional anisotropy, P = .006; mean diffusivity, P < .001). Mean diffusivity was associated with neurocognitive impairment including in the genu of the corpus callosum (P = .04), corona radiata (P = .02), and superior fronto-occipital fasciculi (P = .02).CONCLUSIONS: Leukoencephalopathy during active therapy and neurocognitive impairment at long-term follow-up are associated with microstructural white matter integrity. DTI may be more sensitive than standard MR imaging for detection of clinically consequential white matter abnormalities in childhood acute lymphoblastic leukemia survivors treated with chemotherapy and in children undergoing treatment.ALLacute lymphoblastic leukemia